2011
DOI: 10.4103/0301-4738.81050
|View full text |Cite
|
Sign up to set email alerts
|

Massive retinal gliosis: An unusual case with immunohistochemical study

Abstract: Massive retinal gliosis (MRG) is a rare, benign intraocular condition that results from the proliferation of well-differentiated glial cells. Immunohistochemically, these cells show positivity for glial fibrillary acid protein (GFAP), neuron specific enolase (NSE), and S-100 protein. We encountered a case of a 45-year-old female with loss of vision in the left eye. She had a history of trauma to that eye two years ago. Enucleation was carried out, because malignancy was suspected due to retinal calcification. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Retinal gliosis seen in felines in this series was often profound, at times resembling that seen in human massive retinal gliosis. 3 Massive retinal gliosis is a nonneoplastic proliferation of retinal glial cells in the human retina attributed to a range of factors, including retinal injury, congenital retinal disease, inflammation, retinal vascular disorders, and intraocular neoplasia, 18 some of which were identified in this series of feline FNV. An increase in GFAP expression by Müller glia occurs following experimental retinal detachment in cats, 4 and GFAP and vimentin are upregulated in retinal gliosis attributed to Müller glial cells secondary to retinal disease or trauma.…”
Section: Discussionmentioning
confidence: 91%
“…Retinal gliosis seen in felines in this series was often profound, at times resembling that seen in human massive retinal gliosis. 3 Massive retinal gliosis is a nonneoplastic proliferation of retinal glial cells in the human retina attributed to a range of factors, including retinal injury, congenital retinal disease, inflammation, retinal vascular disorders, and intraocular neoplasia, 18 some of which were identified in this series of feline FNV. An increase in GFAP expression by Müller glia occurs following experimental retinal detachment in cats, 4 and GFAP and vimentin are upregulated in retinal gliosis attributed to Müller glial cells secondary to retinal disease or trauma.…”
Section: Discussionmentioning
confidence: 91%
“…While MRG and astrocytic hamartoma tend to occur in the peripheral retina, acquired retinal astrocytoma generally arises from the optic disc or retinal juxtapapillary area [5,7,8]. In the current patients, the tumor in case 1 arose from the periphery of the retina, while in case 2, it arose from the ora serrata.…”
Section: Discussionmentioning
confidence: 66%
“…Since it is impossible to distinguish the tumor pathologically, the clinical features play an important role in the diagnosis. MRG is a non-neoplastic tissue that occurs in response to eye disorders such as inflammation, trauma or infection [5]. The presence of MRG pathology indicates previous retinal inflammation, retinal pigment epithelial proliferation and calcification [2,5].…”
Section: Discussionmentioning
confidence: 99%
“…These elongated oval or spindle-shaped cells contain varying amounts of fibrillated eosinophilic cytoplasm and show diffuse immunopositivity for GFAP [1,5,20,21,22,23]. Previous electron microscopy studies demonstrated features consistent with astrocytes, with absence of the abundant smooth and rough endoplasmic reticulum and interdigitating villous processes characteristic of Müller cells [4,24].…”
Section: Discussionmentioning
confidence: 99%